因式分解a(a-1)(a-2)-6
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 08:04:16
因式分解a(a-1)(a-2)-6因式分解a(a-1)(a-2)-6因式分解a(a-1)(a-2)-6a(a-1)(a-2)-6=a^3-3a^2+2a-6=a^2(a-3)+2(a-3)=(a^2+
因式分解a(a-1)(a-2)-6
因式分解a(a-1)(a-2)-6
因式分解a(a-1)(a-2)-6
a(a-1)(a-2)-6
=a^3-3a^2+2a-6
=a^2(a-3)+2(a-3)
=(a^2+2)(a-3)
a^3-2a^2-a^2+2a+6
=a^3+a^2+2a+6
因式分解a(a-1)(a-2)-6
a^2-a-6因式分解
(a-5)(a-2)+6-a 因式分解,
因式分解 a^3+a^2-a-1
因式分解:a-a-a+1
a(a-1)(a-2)(a-3)(a-4)因式分解
a^3-a^2-a+1 因式分解a^3-a^2-a+1因式分解
(1)6a^2+ab-2b^2-a+11b-15 因式分解(2)1+a+a(1+a)+a(1+a)^2+a(1+a)^3 因式分解
(2a+1)²因式分解
因式分解a3-2a+1
1-4a^2 因式分解
因式分解 a^-1/6a-1/6
因式分解 (3-a)^2-2a+6
因式分解:6a^2-2a
-9a²-6a-1因式分解
因式分解:a^2-5a+6
因式分解2a平方-7a-6
a^4-5a^2-6因式分解